Development of White Goods Parts in a Concurrent Engineering Environment Based on DFM/DFA Concepts - Canciglieri Junior, Osiris; Buiarskey Kovalchuk, Joao Pedro; Rudek, Marcelo; Souza, Teofilo Miguel de [UNESP]; Pokojski, J.; Fukuda, S.; Salwinski, J. (Springer, 2010)
The classical way to manage the product development processes for massive production has been changing as the high pressure for cost reduction, higher quality standards and market seeking for innovation lead to the necessity of new tools for development control. This context and the learning from the automotive, aerospace industries and others segments were the starting point to understand and apply manufacturing and assembly oriented designs to ease the task of generate goods and from this to obtain at least part of the expected results. This paper demonstrates the applicability of the concepts of Concurrent Engineering and DFM/DFA (Design for Manufacturing and Assembly) in the development of products and parts for the White Goods industry in Brazil (major appliances as refrigerators, cookers and washing machines), showing one case concerning to the development and releasing of a component. Finally, it shows, shortly, how using these techniques as a solution had provided cost savings and reduction in delivery time.
Keywords: Concurrent Engineering; DFM/DFA; Design Management; White Goods; Product Development; Interoperability